Population Genetic Structure of Listeria monocytogenes Strains Isolated From the Pig and Pork Production Chain in France - Félix, Benjamin; Feurer, Carole; Maillet, Aurelien; Guillier, Laurent; Boscher, Evelyne; Kerouanton, Annaëlle; Denis, Martine; Roussel, Sophie (Frontiers in Microbiology, 2018)
Abstract Listeria monocytogenes is an ubiquitous pathogenic bacterium, transmissible to humans through the consumption of contaminated food. The pork production sector has been hit hard by a series of L. monocytogenes-related food poisoning outbreaks in France. An overview of the diversity of strains circulating at all levels of the pork production chain, from pig farming to finished food products, is needed to identify the contamination routes and improve food safety. Until now, no typing data has been available on strains isolated across the entire pig and pork production chain. Here, we analyzed the population genetic structure of 687 L. monocytogenes strains isolated over the last 20 years in virtually all the French départements from three compartments of this production sector: pig farming (PF), the food processing environment (FPE) and finished food products (FFP). The genetic structure was described based on MLST clonal complexes (CCs). The CCs were obtained by mapping the PFGE profiles of the strains. The distribution of CCs was compared firstly between the three compartments and then with CCs obtained from 1106 strains isolated from other food production sectors in France. The predominant CCs of pig and pork strains were not equally distributed among the three compartments: the CC37, CC59 and CC77 strains, rarely found in FPE and FFP, were prevalent in PF. The two most prevalent CCs in the FPE and FFP compartments, CC9 and CC121, were rarely or never detected in PF. No CC was exclusively associated with the pork sector. Three CCs (CC5, CC6, CC2) were considered ubiquitous, because they were observed in comparable proportions in all food production sectors. The two most prevalent CCs in all sectors were CC9 and CC121, but their distribution was disparate. CC9 was associated with meat products and food products combining several food categories, whereas CC121 was not associated with any given sector. Based on these results, CC121 is likely able to colonize a larger diversity of food products than CC9. Both CCs being associated with the food production suggests, that certain processing steps, such as slaughtering or stabilization treatments, favor their settlement and the recontamination of the food